2019
DOI: 10.15244/pjoes/93742
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and Properties of Acid-Soluble Collagen and Pepsin-Soluble Collagen from Silver Carp (Hypophthalmichthys molitrix) Scales: Prerequisite Information for Fishery Processing Waste Reuse

Abstract: As a waste of the fish processing industry, scales cause the disposal of large amounts of solid waste into the environment. How to turn such waste into a useful product is an important issue. In this study, acid-soluble collagen (ASC) and pepsin-soluble collagen (PSC) were extracted from silver carp (Hypophthalmichthys molitrix) scales using a new acid-enzyme combined method. The results showed that the extraction yields of ASC and PSC were 5.09% and 12.06%, respectively. Then amino acid analysis, sodium dodec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…These results were higher than what was found by Bhagwat & Dandge (2016) when extracting collagen by acidic method from the scales of common carp, which amounted to 9.79%. Wu et al (2019) found that the collagen yield of Hypophthalmichthys molitrix fish scales was 5.09. Matmaroh et al (2011) reported that the yield of collagen extracted by the enzymatic method from the scales of the golden-spotted goatfish Parupeneus heptacanthus was 1.20%.…”
Section: Yield and Protein Content Of The Collagenmentioning
confidence: 99%
“…These results were higher than what was found by Bhagwat & Dandge (2016) when extracting collagen by acidic method from the scales of common carp, which amounted to 9.79%. Wu et al (2019) found that the collagen yield of Hypophthalmichthys molitrix fish scales was 5.09. Matmaroh et al (2011) reported that the yield of collagen extracted by the enzymatic method from the scales of the golden-spotted goatfish Parupeneus heptacanthus was 1.20%.…”
Section: Yield and Protein Content Of The Collagenmentioning
confidence: 99%
“…Moreover, the distribution of molar mass, structure and composition, and the subsequent functional features and properties of collagen, depend on the processing conditions of the raw materials from which it is derived like red snapper (lutjnus sp.) [18], sharp nose stingray (Dasyatis Zugei) [12], silver carp (hypophthalmichthys matrix) scales [19], chicken skin [20], small-spotted catshark (S canicular) [21], guina pig [22], "Kacang" goat skin [23] and the method used in the extraction process with or without telopeptides [20], acid soluble and pepsin soluble methods, hydrolysate extraction from chromed leather wastes [1,24]. Thus, it is necessary to determine the appropriate extraction process for each raw material in order to obtain the best performance and the best collagen characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is necessary to determine the appropriate extraction process for each raw material in order to obtain the best performance and the best collagen characteristics. Collagen can be extracted from skin/hide by chemical hydrolysis and enzymatic hydrolysis [25,19]. The enzymatic processes generate less waste; however, it is costly and need a longer time for its effectiveness [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to the ionic bonds, hydrogen bonds, vander Waals bonds, and hydrophobic bonds between molecules [5] , it is difficult for collagen to be dissolved in water or conventional solvent. At present, soluble collagen could be mainly dissolved in acid solution [6] , neutral salt solution [7] , and ionic liquids [8] . These complex solvent systems limit the processing of collagen-based materials.…”
Section: Introductionmentioning
confidence: 99%